Perbedaan Kualitas Gambar MRI 0,3 Tesla Antara Metode Grappa dan Metode Perubahan Nilai Parameter dengan Metode Rutin (Studi Pada Pemeriksaan MRI Vertebra Lumbal Potongan Sagital T2 FSE RSUD Prof. Dr. Margono Soekardjo Purwokerto Pada Pasien Dengan Lumbar - Panji Wibowo Nurcahyo; Ari Suwondo; Hermina Sukmaningtyas (Poltekkes Kemenkes Semarang, 2015)
Background : Artefact degrade image quality. Motion artefact can be minimized by reducing scan time. The use of GRAPPA and change the value of TR, NEX and phase enchoding can reduce scan time. This study aims to determine the difference between MRI image quality of the GRAPPA method and routine method with change the value Phase enc. Dir., FOV phase, TR, TE, NEX, concatenation, base resolution, phase resolution and bandwidth by routine method MRI examination of lumbar spine sagittal T2 FSE in Prof. Dr. Margono Soekardjo hospital in patients with lumbar disorders.Methods : Quasi experiments with equivalent posttest only control group design in 25 respondents were obtained in consecutive sampling. Each respondent was given three treatments with different method. Qualitative assessment was done on the MRI images results of the third treatment. Presence or absence of an overview assessment results HNP, spondylosis and degenerative disc analyzed with Cochran test while the level of clarity of the ligamentum flavum, thecal sac, intervertebral disc, vertebral body and the spinal cord was analyzed by Friedman test.Results : Cochran test produces a p value 0,05, while the friedman test results were followed by post hoc analysis resulted p value 0,05. The highest mean value rank is 3 with obtained of the routine method but has a scan time 326 seconds, the GRAPPA activation performed (mean rank 1) then the scan time can be reduced by 144 second and routine method with change the value of some parameters can reduce 150 second with a mean rank 2.Conclusion : There is no difference reveal HNP, spondilosis and degenerative disc ability between GRAPPA method and routine method with change the value of some parameters by routine methodProf. Dr. Margono Soekardjo hospital, but levels of clarity ligamentum flavum, thecal sac, intervertebra disc, corpus vertebra dan spinal cord is difference. Routine method Prof. Dr. Margono Soekardjo hospitalproduce images with the best quality, but has a maximum scan time.